VENETOCLAX IN TREATMENT OF CHRONIC LYMPHOCYTIC LEUKEMIA (literature review) - T. E. Byalik (Онкогематология)
In recent years, great progress has been made in understanding biology and pathogenesis of chronic lymphocytic leukemia. The key thing in disease pathogenesis is the apoptosis resistance of tumor cells. One of the main regulators of programmed cell death is the Bcl-2 family proteins. Important role of Bcl-2 protein in carcinogenesis made it an attractive target for therapeutic intervention. This review focuses on venetoclax (a selective inhibitor of the anti-apoptotic Bcl-2 protein) in the treatment of chronic lymphocytic leukemia.